Media Komunikasi dalam Peran Dakwah - Efendi, Erwan; Faruq, Muhammad; Amalia, Sylvia; Syakira, Nayaka; Aini, Azizah; Khairunnisa, Farida (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Da'wah patterns have changed over time. Written sermons have now become more important and effective than oral sermons. Especially for works that contain preaching messages and social media. The benefit of da'wah using this model is that as Rasulullah SAW once said, "Indeed, the ink of the ulama is better than the blood of the martyrs", does not mean that the content of the da'wah will disappear even though the preacher or writer has died. Analysis of the impact of media on the growth of Islamic Da'wah is the aim of this research. This research approach uses qualitative techniques derived from actual field data. It is proven that Allah SWT requires da'wah to other humans when He states in the QS. Saba':28, "And we did not send you but to all mankind as a bearer of good news and as a warning, but most people do not know." The study presented in the findings of this paper shows that the use of mass media as a channel for da'wah offers advantages. This shows the importance of media involvement in spreading religious beliefs among society.